Alpha linolenic acid intake alleviates myocardial ischemia/reperfusion injury via the P2X7R/NF-κB signalling pathway. (October 2018) - Wang, Shuo; Liu, Chaxian; Gong, Chengxin; Li, Tao; Zhao, Jiani; Xiao, Wen; Liu, Yuanyuan; Peng, Shanping; Xiong, Chaopeng; Wang, Rumeng; Ding, Lu; Liu, Xingzi; et al.
Graphical abstract: Highlights: ALA dose-dependently protected myocardium against I/R injury. ALA dose-dependently inhibited TNF-α and IL-1β production in I/R myocardium. ALA hampered P2X7R activation via bonding with Ser101 and Tyr291 residues. ALA dose-dependently attenuated P2X7R activation and prevented the NF-κB activation. Abstract: This study investigated the protective role of α-linolenic acid (ALA) in myocardial ischemia/reperfusion (MI/R) injury. ALA was indicated to dose-dependently protect myocardium against I/R injury, attenuate purinergic P2X7 receptor (P2X7R) activation, prevent NF-κB activation, and inhibit tumor necrosis factor (TNF)-α and interleukin-1β (IL-1β) production in I/R myocardium. Overexpression of P2X7R enhanced NF-κB activation, inflammation and MI/R injury, which could be alleviated by ALA. In vitro hypoxia/reoxygenation (H/R) H9c2 cells, ALA could also inhibit P2X7R activation, NF-κB activation and TNF-α and IL-1β production. Molecular docking analysis indicated ALA may hamper the activation of P2X7R. The functional relevance of ALA directly regulated P2X7R and the subsequent NF-κB signalling was supported by inhibition of P2X7R with A438079 (P2X7R antagonist) as well as suppression of NF-κB by PDTC (NF-κB inhibitor) in H9c2 H/R cells transfected with pcDNA3.0-P2X7R plasmid. These findings demonstrated that ALA attenuates inflammation and MI/R injury through down-regulating P2X7R/NF-κB signalling pathway.